New uniqueness results for boundary value problem of fractional differential equation - Cui, Yujun; Ma, Wenjie; Sun, Qiao; Su, Xinwei (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, uniqueness results for boundary value problem of fractional differential equation are obtained. Both the Banach's contraction mapping principle and the theory of linear operator are used, and a comparison between the obtained results is provided.
Keywords: fractional differential equation; uniqueness results; Banach's contraction mapping principle